2021
DOI: 10.3389/fonc.2021.664916
|View full text |Cite
|
Sign up to set email alerts
|

HOTTIP Enhances Gemcitabine and Cisplatin Resistance Through Sponging miR-637 in Cholangiocarcinoma

Abstract: Chemo-resistance prominently hampers the effects of systemic chemotherapy to cholangiocarcinoma (CCA). Long non-coding RNAs (lncRNAs) have been shown to have great importance not only in tumorigenesis but also in therapeutic prognosis. The aim of this study is to investigate the role of lncRNA HOTTIP in the chemo-resistance to cisplatin and gemcitabine (CG) in CCA. The upregulated expression of HOTTIP was observed in CCA patients and the upregulation was associated with therapeutic responsiveness and prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Most of the lncRNA-related research has focused on the mechanism and function of dysregulated lncRNAs in the tissues and cells of CCA. The following lncRNAs have been documented to be linked to the prognosis of cholangiocarcinoma ( Table 2 ): ANRIL ( Angenard et al, 2019 ), ASAP1-IT1 ( Guo et al, 2018 ), CCAT1 ( Zhang et al, 2017a ), CCAT2 ( Xu et al, 2018a ), CRNDE ( Xia et al, 2018 ), FOXD2-AS1 ( Hu et al, 2022 ), GAPLINC ( Wang et al, 2018 ), H19 ( Xu et al, 2017a ), HOTAIR ( Qin et al, 2018 ), HOTTIP ( Gao et al, 2021 ), HOXD-AS1 ( Li et al, 2020b ), LINC00261 ( Gao et al, 2020 ), LINC00665 ( Lu et al, 2021 ), LINC00667 ( Li et al, 2021a ), LINC01296 ( Zhang et al, 2018a ), LOXL1-AS1 ( Zhang et al, 2019a ), NNT-AS1 ( Huang et al, 2019a ), MALAT1 ( Tan et al, 2017 ), PAICC ( Xia et al, 2020 ), PANDAR ( Xu et al, 2017b ), PCAT1 ( Sun et al, 2021 ), lnc-PKD2-2-3 ( Qiu et al, 2019 ), SNHG3 ( Tian et al, 2019 ), Sox2ot ( Li et al, 2018 ), TUG1 ( Xu et al, 2017c ), UCA1 ( Xu et al, 2017d ), ZEB1-AS1 ( Jiang et al, 2020a ), ZFAS1 ( Li et al, 2019c ).…”
Section: Lncrnas As Diagnostic and Prognostic Biomarkers In Cholangio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the lncRNA-related research has focused on the mechanism and function of dysregulated lncRNAs in the tissues and cells of CCA. The following lncRNAs have been documented to be linked to the prognosis of cholangiocarcinoma ( Table 2 ): ANRIL ( Angenard et al, 2019 ), ASAP1-IT1 ( Guo et al, 2018 ), CCAT1 ( Zhang et al, 2017a ), CCAT2 ( Xu et al, 2018a ), CRNDE ( Xia et al, 2018 ), FOXD2-AS1 ( Hu et al, 2022 ), GAPLINC ( Wang et al, 2018 ), H19 ( Xu et al, 2017a ), HOTAIR ( Qin et al, 2018 ), HOTTIP ( Gao et al, 2021 ), HOXD-AS1 ( Li et al, 2020b ), LINC00261 ( Gao et al, 2020 ), LINC00665 ( Lu et al, 2021 ), LINC00667 ( Li et al, 2021a ), LINC01296 ( Zhang et al, 2018a ), LOXL1-AS1 ( Zhang et al, 2019a ), NNT-AS1 ( Huang et al, 2019a ), MALAT1 ( Tan et al, 2017 ), PAICC ( Xia et al, 2020 ), PANDAR ( Xu et al, 2017b ), PCAT1 ( Sun et al, 2021 ), lnc-PKD2-2-3 ( Qiu et al, 2019 ), SNHG3 ( Tian et al, 2019 ), Sox2ot ( Li et al, 2018 ), TUG1 ( Xu et al, 2017c ), UCA1 ( Xu et al, 2017d ), ZEB1-AS1 ( Jiang et al, 2020a ), ZFAS1 ( Li et al, 2019c ).…”
Section: Lncrnas As Diagnostic and Prognostic Biomarkers In Cholangio...mentioning
confidence: 99%
“…Recently, studies have identified lncRNAs as important players in CCA chemoresistance. So far, a few novel lncRNAs, including NEAT-1, LINC01714, HOXD-AS1, HOTTIP, LINC00665, and lnc-PKD2-2-3, have been revealed to modulate chemoresistance in CCA ( Figure 2 ) ( Lu et al, 2021 ; Qiu et al, 2019 ; Li et al, 2020b ; Gao et al, 2021 ; Parasramka et al, 2017 ; Shen et al, 2020 ). These resistance-associated lncRNAs present new opportunities for the treatment of CCA.…”
Section: The Role Of Lncrnas In the Therapeutic Target Of Cholangioca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Long non-coding RNA (lncRNA), as a newly discovered type of RNA in the current century with a length of more than 200 bp but less protein-coding ability, has been discovered to be closely involved in the pathogenesis of various cancers (11)(12)(13)(14). In the aspect of CCA, several specific lncRNAs have been discovered to participate in CCA initiation or progression (15)(16)(17)(18). For instance, lncRNA SNHG3 promotes CCA cell proliferation and migration via mediating the miR-3173-5p/ERG axis (15); lncRNA FAM66C induces CCA growth, mobility, and glycolysis by modifying miR-23b-3p/KCND2 in vitro and in vivo (16); and lncRNA HOTTIP elevates drug resistance of gemcitabine and cisplatin via sponging miR-637 in CCA (18).…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of CCA, several specific lncRNAs have been discovered to participate in CCA initiation or progression (15)(16)(17)(18). For instance, lncRNA SNHG3 promotes CCA cell proliferation and migration via mediating the miR-3173-5p/ERG axis (15); lncRNA FAM66C induces CCA growth, mobility, and glycolysis by modifying miR-23b-3p/KCND2 in vitro and in vivo (16); and lncRNA HOTTIP elevates drug resistance of gemcitabine and cisplatin via sponging miR-637 in CCA (18). However, the engagement of a great number of lncRNAs in CCA is not dragged out, and comprehensive exploration is lacking.…”
Section: Introductionmentioning
confidence: 99%